Exploring the Standardized Root Mean Square Residual (SRMR) of Factors Influencing E-book Usage among CCA Students in the Philippines - Pinedaa, Angelica Jaisel M.; Mohamadc, Almira N.; Solomon, Oluyinka; Bircob, Christal Nicole H.; Superioe, Mark Gil; Cuencof, Heidie O.; Bognot, Filipinas L. (SAINTIS Publishing, 2022)
Early adopters of e-books claimed that e-books encouraged reading, and served as a means of improving individual academic performance. This appears to be unnoticed by academics in the Philippines. Objectives: The primary goal of this work is to conduct a study reporting the standardized root mean square residual (SRMR) of factors influencing e-book usage among students and robustness of the Technology Acceptance Model (TAM). Design: The TAM criteria were used to design an online questionnaire survey focusing on the usefulness, ease of use perception, and attitude toward addressing the hypotheses to the structural equation model for using e-books. The questionnaire’s validity was confirmed by four specialists. The participants are undergraduates at City College of Angeles, Philippines. A total of 348 responses was analyze with aids of SmartPLS version 3.3.2. Results show that these four factors are related to each other and have a strong influence on e-book usage and adoption. Also indicated that perceived usefulness (PU) is the most significant and perceived ease of use (PEU) indicated the least supported. A total 65% variance explained, SRMR 0.08 NFI above 0.9 and RMS_theta 0.12 achieved. Ultimately, a thorough analysis of the study is recommended for future researchers.